2008
DOI: 10.1363/3404008
|View full text |Cite
|
Sign up to set email alerts
|

Severity and Cost of Unsafe Abortion Complications Treated in Nigerian Hospitals

Abstract: Abortion is legally restricted in most African countries, and in Nigeria it is permitted only to save the life of a pregnant woman. Nevertheless, the practice is common: According to an estimate based on a 1996 national survey of physicians and hospitals in Nigeria, 610,000 abortions occurred in a one-year period, a rate of about 25 abortions per 1,000 women of childbearing age (15-44 years). 1 This study also found that 27% of physicians in private practice performed abortions despite the legal restrictions.A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 4 publications
6
60
1
Order By: Relevance
“…Henshaw and colleagues found that in Nigeria, women who receive treatment for complications of unsafe abortion pay more for care than do those who are treated for miscarriage (US$116 vs. US$43). 13 Another…”
mentioning
confidence: 99%
“…Henshaw and colleagues found that in Nigeria, women who receive treatment for complications of unsafe abortion pay more for care than do those who are treated for miscarriage (US$116 vs. US$43). 13 Another…”
mentioning
confidence: 99%
“…These were the reasons given by our patient; the same reasons given by patients who seek to terminate pregnancies especially in Nigeria [6]. This case occurred in the Northern region of Nigeria, which has been reported to have the largest proportion of complications of induced abortion caused by physicians who are mostly untrained to do this procedure [8]. The physician involved in this case was a newly qualified doctor posted to the rural hospital who was just 'helping' out a pitiful young woman.…”
Section: Discussionmentioning
confidence: 57%
“…Women who had abortion complications observed that many doctors were not well trained on how to carry out abortion procedures and post abortion care [8]. This highlights the need for training of doctors on how to do the procedure properly.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 47,000 women will die as a result of unsafe abortion [42]. A study finds that more than 3,000 Nigerian women being treated in hospitals for complications from such procedures die each year [48]. In Argentina and Chile, more than one third of maternal deaths among adolescents are due to complications of unsafe abortions [49].…”
Section: K Delayed Marriage and Abortionmentioning
confidence: 99%